2017
DOI: 10.1371/journal.pone.0177465
|View full text |Cite|
|
Sign up to set email alerts
|

Discerning morpho-anatomical, physiological and molecular multiformity in cultivated and wild genotypes of lentil with reconciliation to salinity stress

Abstract: One hundred and sixty two genotypes of different Lens species were screened for salinity tolerance in hydroponics at 40, 80 and 120 mM sodium chloride (NaCl) for 30 d. The germination, seedling growth, biomass accumulation, seedling survivability, salinity scores, root and shoot anatomy, sodium ion (Na+), chloride ion (Cl-) and potassium ion (K+) concentrations, proline and antioxidant activities were measured to evaluate the performance of all the genotypes. The results were compared in respect of physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 57 publications
(54 reference statements)
7
44
0
Order By: Relevance
“…Intact pericycle and steler region of tolerant genotypes also helped in reducing the ion absorption. Similar observations were also made in lentil [ 36 ], finger millet [ 23 ] and Lotus tenuis [ 11 ]. Similarly, the shoot had thick epidermis in tolerant genotypes compared sensitive ones.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Intact pericycle and steler region of tolerant genotypes also helped in reducing the ion absorption. Similar observations were also made in lentil [ 36 ], finger millet [ 23 ] and Lotus tenuis [ 11 ]. Similarly, the shoot had thick epidermis in tolerant genotypes compared sensitive ones.…”
Section: Discussionsupporting
confidence: 81%
“…This trait has been widely used parameter for selecting salt-tolerant lines and cultivars [ 35 ]. Breeding for seedling survival and vigorous growth has been argued to be agronomically most effective approach for increasing yield under saline soils [ 36 ]. Alkalinity stress at 40 mM NaHCO 3 had affected the seedling survival in all the genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of 100 accessions of L. culinaris subsp. orientalis under hydroponic culture at 120‐mM NaCl concentration resulted in the identification of several donors for salinity tolerance (Singh et al, 2017). Importantly, flowering and growth responses of wild Lens to light quality have also been studied (Yuan, Saha, Vandenberg, & Bett, 2017).…”
Section: Lentilmentioning
confidence: 99%
“…Earlier studies have indicated that the lentil crop is sensitive to salinity stress (Ashraf & Waheed, 1990). Significant genetic variation for salinity tolerance prevails among the genotypes of lentil (Singh et al., 2017). The development of saline tolerant cultivars can be an appropriate approach for minimizing yield losses under salinity stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Various physiological and biochemical traits like seedling survivability, salinity score, seedling growth and biomass, Na + and Cl − accumulation, production of H 2 O 2, antioxidant activities etc. have been used for characterization of salinity tolerance at the seedling stage in crop plants (Singh et al., 2017; Singh et al., 2018a; Singh et al., 2018b). Among the above traits, seedling survivability and FDA based fluorescent signals (indicating production of H 2 O 2 ) are the major traits to visually distinguish between salt‐tolerant and salt‐sensitive genotypes (Singh et al., 2017).…”
Section: Introductionmentioning
confidence: 99%